Supportive care utilization and treatment toxicity in children with Down syndrome and acute lymphoid leukaemia at free‐standing paediatric hospitals in the United States. (10th May 2016) - Salazar, Elizabeth G.; Li, Yimei; Fisher, Brian T.; Rheingold, Susan R.; Fitzgerald, Julie; Seif, Alix E.; Huang, Yuan‐Shung; Bagatell, Rochelle; Aplenc, Richard
Summary: Although inferior outcomes of children with Down syndrome (DS) and acute lymphoid leukaemia (ALL) are established, national supportive care patterns for these patients are unknown. A validated retrospective cohort of paediatric patients diagnosed with ALL from 1999 to 2011 was assembled from the US Pediatric Health Information System (PHIS) database to examine organ toxicity, sepsis, and resource utilization in children with and without DS. Among 10699 ALL patients, 298 had DS‐ALL (2·8%). In a multivariate model, DS was associated with increased risk of cardiovascular (odds ratio [OR] 2·0, 95% confidence interval [CI] 1·6–2·7), respiratory (OR 2·1, 95% CI: 1·6–2·9), neurologic (OR 3·4, 95% CI 1·9–6·2), and hepatic (OR 1·4, 95% CI 1·0–1·9) dysfunction and sepsis (OR 1·8, 95% CI: 1·4–2·4). Children with DS‐ALL used significantly more respiratory support, insulin, and anti‐infectives, including broad‐spectrum Gram‐positive agents, quinolones, and azoles. They used significantly fewer analgesics and antiemetics compared to non‐DS‐ALL children. Ultimately, this study confirms the increased risk of infectious and end‐organ toxicity in children with DS‐ALL and quantifies important differences in resource utilization between children with DS and non‐DS ALL. These findings highlight the importance of investigating the impact of these care variations and developing specific supportive care guidelines for this population.